Implementasi Program Corporate Social Responsibility PT. Pertamina Terhadap Pemulihan Bisnis UMKM Binaan Akibat Pandemi Covid-19 - Bharata Dharmacahya; Dwiningtyas Padmaningrum; Agung Wibowo (Fakultas Pertanian Universitas Jember, 2022)
The pandemic of Covid-19 has become a problem for SMEs in Indonesia. SMEs experience a shortage of labor which causes people to lose income. PT Pertamina through Corporate Social Responsibility offers assistance to tackling the problems faced by SME actors during the pandemic by running partnership and community development program. The goal is to help SMEs to be able to survive and develop their businesses in pandemic situation. This study aims to determine the form, the stages and the performance of PT. Pertamina CSR implementation in the process of recovering the SME businesses causes by the pandemic. The basic research method uses a qualitative descriptive method. The location and informant selection was carried out purposively. Research data obtained from observation, interviews and documentation. The validity of the research using the method and source triangulation technique. The results of the study found that the form of the CSR program implemented by PT. Pertamina from before the pandemic until now has not experienced any changes, namely community development. CSR implementation by PT. Pertamina didn’t find any changes from before and during this pandemic, but what has been done in this pandemic situation is adjustment of activities. The adjustments are intensively carried out by PT. Pertamina in this pandemic is to encourage the digitization of SMEs. CSR Implementation of PT. Pertamina is carried out in four stages, starting from planning, implementation, evaluation and reporting. CSR Performance of PT. Pertamina during the pandemic can be seen through eight CSR performance indicators, namely leadership, aid proportion, transparency and accountability, area coverage, planning and evaluation, stakeholder involvement, sustainability and outcome